Who ate all the squid? : football adventures in South Korea - Rowcliffe, Devon (Durrington : Pitch Publishing, 2020)
When a struggling Korean football club wants to transform its fortunes, who does it turn to? A former Chelsea manager and a trio of players with Premier League experience, of course. Who Ate All the Squid?: Football Adventures in South Korea charts the year Ian Porterfield managed faltering K League giant Busan IPark. The Sunderland FA Cup legend lured three players from English football out to Korea: striker Jamie Cureton, an ex-England youth international who turned down Manchester United; Andy Cooke, a former Burnley and Stoke City forward who started his career building cowsheds; and Jon O
Keywords: Korean football